2014
DOI: 10.2399/jmu.2014001002
|View full text |Cite
|
Sign up to set email alerts
|

Radiological evaluation of septal bone variations in the sphenoid sinus

Abstract: ÖzetAmaç: Sfenoid sinüste yer alan septum, optik sinir ve internal karotid arter ile ilgili olarak varyatif durumlar›n belirlenmesi.Yöntem: Akut/kronik sinüzit tan›s›yla paranasal sinüs bilgisayarl› tomografi istenen 218 hasta retrospektif olarak taranm›flt›r. Bu hastalar›n tomografileri aksiyel ve koronal kesitlerde incelenerek sfenoid sinüs, kemik septa varyasyonlar›, say› ve uzan›m flekli yönünden s›n›f-land›r›lm›fl, ayr›ca optik sinir ve internal karotid arter protrüzyon valanslar› hesaplanm›flt›r.Bulgular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…These results were different from other findings, possibly due to the presence of racial or anatomographical variants across different geographical or ancestral origins that might show the evolution of anatomical variations along ethno-geographical or racial diversity. In our study, the absence of septa was found in only 1% of the patients, while it was 2.7% in Nigerians [4,31] and 2.2% in other studies [32][33][34]. These findings are almost comparable despite the difference in their sample size.…”
Section: Discussionsupporting
confidence: 49%
“…These results were different from other findings, possibly due to the presence of racial or anatomographical variants across different geographical or ancestral origins that might show the evolution of anatomical variations along ethno-geographical or racial diversity. In our study, the absence of septa was found in only 1% of the patients, while it was 2.7% in Nigerians [4,31] and 2.2% in other studies [32][33][34]. These findings are almost comparable despite the difference in their sample size.…”
Section: Discussionsupporting
confidence: 49%
“…12 World literature shows great variation in the prevalence of more than one intrasphenoid sinus septations from as high as 95% to as low as 7.1%. 8,9,[12][13][14][15] Double septa were found in 11% in present study and more than 2 septa in 3.4%. The attributable factor for these variations seems to be small sample size in majority of these studies.…”
Section: Resultsmentioning
confidence: 54%
“…They also reported that there was a significant difference in the mean distances between the deviated sphenoid septum and the internal carotid arteries deviation to the opposite sides. Dunder et al, (16) Thakur et al, (21) conducted a study in Uttarakhand, India and reported that their study includes 60.5% of male participants with 89.5% of cases with sellar type of pneumatization and single intersinus septum was noted among 68% of cases. These findings are consistent with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%